تركيب عناصر حساسة لتحديد غاز كبريت الهيدروجين في البيئة المحيطة - معروف محمد (Latakia University Journal -Basic Sciences Series, 2018)
درست مشكلة تركيب بنى غير متجانسة زجاجية المظهر على أساس مزيج مؤلف من أكسيدي البزموت والبور. إذ تمكنا من وضع طريقة محددة لتشكيل طبقة منشطة من الفوسفات ، التي رسبت على سطح المادة الزجاجية ، بعد رشها بمحلول مشبع من موليبدو حمض الفوسفور ومحلول مشبع من باراموليبدات الأمونيوم. استطعنا بوساطة العناصر الحساسة التي قمنا بتركيبها ، تحديد محتوى غاز كبريت الهيدروجين في البيئة المحيطة وذلك عن طريق قياس الناقلية الكهربائية للعنصر الحساس الملامس للهواء الذي تتراوح كمية غاز كبريت الهيدروجين فيه ، من 4 mg/m3 إلى 60 mg/m3 بخطأ معياري نسبي لايزيد عن 0.03 . A study has been made about the problem of hidropolycompounds HPC, having glass appearance, consisting of Bismuth and Boron Oxides. We could set a definite method system to form an activating layer from the phosphate, sedimented on the surface of the glassy material after spraying it with a saturated solution of phosphoric Acid Molybdenum and saturated solution of Ammonium Paramolybdates. By means of the composed sensory elements we could determine the content of the H2S in the ambient environment, by measuring the conductivity of the sensory element in touch with the air in which the quantity of H2S ranges from 4mg/m3 to 60 mg / m3 with a standard relative error not exceeding 0.03.